Prevalence of latent CMV and EBV infection and their impact on the incidence of upper respiratory infection among athletes: A systematic review and meta-analysis - da Silva, I.; Marmett, B.; Lira, F. [UNESP]; Stein, C.; Madruga, M.; Bauer, M.; Romão, P.; Dorneles, G.; Peres, A. (Elsevier, 2025)
Objective: To summarize the prevalence of cytomegalovirus (CMV) and Epstein-Barr virus (EBV) among athletes and the impact on the incidence of upper respiratory infection (URTI). Data sources and study selection: It was performed a systematic review coupled with meta-analysis using the terms related to athletes and latent infection of CMV and EBV, on MEDLINE/Pubmed, Embase, and Cochrane Library databases. The quality of the included studies was assessed using the JBI Critical Appraisal Checklist for Prevalence Studies and the certainty of evidence (CoE) for point-prevalence estimates was assessed using GRADE. Data synthesis: A total of 30 publications fulfilled the inclusion criteria, 16 references on latent CMV infection and 19 on EBV infection. The prevalence of latent CMV and EBV infections in athletes was 39.27% (95%CI: 29.38–49.58; CoE: Low) and 71.15% (95%CI: 58.65–82.29; CoE: Low), respectively. Prospective studies revealed that latent EBV infection has no impact on the URTI development (RR: 0.87; 95%CI%: 0.73 to 1.03; I2: 2%), or in the previous infection reported by the athletes before engagement in the studies (RR: 1.02; 95%CI: 0.55 to 1.89; I2: 0%). EBV+ athletes who reported URTI presented higher risk to EBV reactivation, evaluated by EBV DNA shedding, than EBV+ athletes without URTI (RR: 1.59; 95%-CI: 1.22 to 2.06); I2: 22%). Conclusion: The results suggested a high prevalence of latent EBV infection in athletes, while less than half of athletes presented CMV seroprevalence. The current data indicate that URTI was associated with higher risk to EBV reactivation in athletes.
Prévalence des infections latentes à CMV et EBV et leur impact sur l'incidence des infections des voies respiratoires supérieures chez les athlètes : une revue systématique et méta-analyse
Keywords: Elite athlete; Latent infection; Virus disease